Effect of coarse initial grain size on microstructure and mechanical properties of weld metal and HAZ of a low carbon steel - Eroglu, M; Aksoy, M; Orhan, N (Elsevier Science Sa, 1999)
In this study, the effects of coarse initial grain size with varying heat inputs on microstructure and mechanical properties of weld metal and heat-affected zone (HAZ) were investigated. In the welding experiments, SAE 1020 steel specimens in hot-rolled and in grain-coarsened conditions were used. The specimens taken from the hot-rolled steel (original) plate were heat treated at 1100 degrees C for 45 min and then cooled in a furnace in order to obtain a coarse initial grain size. The original and grain-coarsened specimens were welded using a submerged are welding machine with heat inputs of 0.5, 1 and 2 kJ/mm. Following the welding, microstructure, hardness and toughness of weld metals and HAZs were investigated. From the results, we tried to establish a relationship between initial grain size, microstructure, hardness and toughness of weld metals and HAZs. From the results of the toughness tests, it was seen that the weld metals of coarse initial grain sized specimens and original specimens exhibited nearly the same toughness values with the same heat input, whereas different HAZ toughness values were obtained with the same heat input. Maximum toughness of HAZ of the coarse initial grain sized specimen was achieved with a high input, while maximum toughness of original specimen was obtained with a medium heat input. As a result, considering the heat input, it was observed that the coarse initial grain size had a great influence on the microstructure, hardness and toughness of HAZ of a low carbon steel. Thus, taking into consideration the plate thickness, a higher heat input should be used with respect to the maximum toughness of the HAZ in the welding of grain-coarsened low carbon steels. (C) 1999 Elsevier Science S.A. All rights reserved.
Keywords: initial grain size; heal-affected zone (HAZ); weld metal (WM); microstructure; toughness; hardness